NEUTROPHILIC DERMATOSIS OF THE DORSAL HANDS – REPORT OF TWO PATIENTS - Macias, Vasco Coelho; Labareda, José; Themido, Rui; Viana, Isabel (Journal of the Portuguese Society of Dermatology and Venereology, 2013)
The concept of neutrophilic dermatoses encompasses several entities that share clinical and histological aspects. Recently described, neutrophilic dermatosis of the dorsal hands is a disease with unknown etiology that clini- cally resembles a localized variant of Sweet syndrome, with lesions predominantly located in the back of the hands and with variable presence of systemic symptoms accompanying. From the histological point of view, it is characterized by a dense neutrophilic inflammatory infiltrate with vasculitis aspects being inconsistent. The authors present two patients with neutrophilic dermatosis of the dorsal hands and discuss its clinical, laboratory and histopathological aspects and therapeutic options available. The neutrophilic dermatosis of the dorsal hands is an evolving concept, which shares many common aspects with other neutrophilic dermatoses, suggesting a continuous spectrum of this group of diseases KEYWORDS – Hand dermatoses; Sweet syndrome.